2021
DOI: 10.3390/toxins13060430
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the Adverse Impacts of Fungal Mycotoxin on Proximate Composition of Feed and Growth Performance in Broilers by Combined Adsorbents

Abstract: Synergistic interaction of adsorbents in reducing the adverse impacts of mycotoxin on performance and proximate composition of broiler feeds was investigated. Fungal growth was induced by sprinkling water on the feed. S. cerevisiae + bentonite, kaolin + bentonite or S. cerevisiea + kaolin adsorbent combinations (1.5 g/kg feed) were added and the feeds were stored in black polythene bags. An untreated group was kept as a positive control while fresh uncontaminated feed was used as a negative control. Mycotoxins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 49 publications
(72 reference statements)
1
9
0
Order By: Relevance
“…Consumption of mycotoxin-contaminated feeds has been reported to cause poor health and performance of chickens as well as mortalities ( Table 3 ); however, there are limited data in the SSA context. Apart from a few studies, mostly conducted in Nigeria [ 50 , 51 ], the impacts are reported from trials conducted in other countries. Effects of a mycotoxin on an animal depend on the mycotoxin type, level and duration of exposure, age, and specie of the animal.…”
Section: Toxicological Impact Of Major Mycotoxins On Experimental Broilers and Layer Chickensmentioning
confidence: 99%
See 2 more Smart Citations
“…Consumption of mycotoxin-contaminated feeds has been reported to cause poor health and performance of chickens as well as mortalities ( Table 3 ); however, there are limited data in the SSA context. Apart from a few studies, mostly conducted in Nigeria [ 50 , 51 ], the impacts are reported from trials conducted in other countries. Effects of a mycotoxin on an animal depend on the mycotoxin type, level and duration of exposure, age, and specie of the animal.…”
Section: Toxicological Impact Of Major Mycotoxins On Experimental Broilers and Layer Chickensmentioning
confidence: 99%
“…Retarded growth resulting from mycotoxin-contaminated feeds results in poultry not attaining the required weights at the required time and thus economic losses as farmers use more feed and time to attain the required weights [ 88 ]. In Nigeria, broilers fed diets contaminated with AFB1 at levels of 34 μg/kg [ 50 ] or 500 μg/kg [ 51 ] had reduced feed intake and body weight (BW) gain compared with birds fed AFs-free diets. Decreased BW and BW gain were reported in broilers fed AFs at levels of 50 to 200 μg/kg [ 64 , 71 , 96 ].…”
Section: Toxicological Impact Of Major Mycotoxins On Experimental Broilers and Layer Chickensmentioning
confidence: 99%
See 1 more Smart Citation
“…Broiler chickens that were fed AFs at levels ranging from 50 to 200 µg/kg experienced a reduction in body weight and a decrease in body weight gain, as reported [ 10 , 42 ]. Birds that were given diets containing either 34 µg/kg or 500 µg/kg of AFB1 experienced a decrease in their body weight gain, in contrast to the birds that were fed diets free from AFs [ 43 , 44 ]. The growth performance of chickens can be influenced by various factors, including the varying concentrations of mycotoxins and their metabolite binders, the origin of mycotoxins, and the specific chicken species.…”
Section: Major Types Of Mycotoxins and Their Masked Forms In Chickensmentioning
confidence: 99%
“…Various strategies can be employed to reduce mycotoxin levels in feed and minimize their harmful effects. These include implementing rigorous quality control measures in the production and storage of feed ingredients [ 43 , 179 ], adopting proper post-harvest practices to limit fungal growth and mycotoxin production [ 180 ], utilizing physical methods such as sorting and cleaning to remove contaminated grains [ 181 ], and employing feed additives such as adsorbents, enzymes, probiotics, prebiotics, antioxidants, and mycotoxin binders. A comprehensive approach that combines preventive measures, monitoring, and appropriate mitigation strategies is essential for managing mycotoxin contamination and safeguarding animal and human health.…”
Section: Approaches To Mitigate Mycotoxins In Poultry Dietsmentioning
confidence: 99%